2017
DOI: 10.1186/s12885-017-3200-1
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised controlled trial to evaluate the efficacy, morbidity and functional outcome of endoscopic transanal proctectomy versus laparoscopic proctectomy for low-lying rectal cancer (ETAP-GRECCAR 11 TRIAL): rationale and design

Abstract: BackgroundTotal mesorectal excision is the standard surgical treatment for mid- and low-rectal cancer. Laparoscopy represents a clear leap forward in the management of rectal cancer patients, offering significant improvements in post-operative measures such as pain, first bowel movement, and hospital length of stay. However, there are still some limits to its applications, especially in difficult cases. Such cases may entail either conversion to an open procedure or positive resection margins. Transanal endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 45 publications
0
74
0
2
Order By: Relevance
“…As TaTME is substantially different from abdominal techniques in terms of open access to the tumour, purse-string closure and a subsequent endoluminal approach to the mesorectal dissection, it is especially important to assess long-term outcomes properly. RCTs such as COLOR III 13 and GRECCAR 11 14 are investigating long-term outcomes of TaTME, and are currently including patients. Recently, concern has been raised by the first report 15 of national Norwegian data which showed an increase in the incidence of local recurrence with an extensive or multifocal pattern following TaTME, leading to a national halt to TaTME 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As TaTME is substantially different from abdominal techniques in terms of open access to the tumour, purse-string closure and a subsequent endoluminal approach to the mesorectal dissection, it is especially important to assess long-term outcomes properly. RCTs such as COLOR III 13 and GRECCAR 11 14 are investigating long-term outcomes of TaTME, and are currently including patients. Recently, concern has been raised by the first report 15 of national Norwegian data which showed an increase in the incidence of local recurrence with an extensive or multifocal pattern following TaTME, leading to a national halt to TaTME 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the TATME technique many authors have suggested, on the basis of retrospective and comparative studies, that this technique must be now considered as the new gold standard, not only for the management of low but also mid or even high rectal cancer [8][9][10][11][12][13][14][15][16]. However, no randomized trial has been reported so far (the COLOR III and the GRECCAR 11 studies are still in progress [17,18]), and some intra-operative complications (including urethral or vaginal injury) have been reported by others, due, at least in part, to the need for a better knowledge of anatomical landmarks, which are different from those used during LTME.…”
Section: Introductionmentioning
confidence: 99%
“…According to reports in the study by Veltcamp and Koedam, quality of life including anal function after taTME was comparable with that after laparoscopic surgery 31,32) . There are two ongoing large randomized controlled trials comparing taTME and LapTME, namely the COLOR III and GRECCAR 11 studies 33,34) . Results of these studies, including long-term outcomes, are awaited for accurately evaluating the efficacy of taTME.…”
Section: Clinical Evidencementioning
confidence: 99%